2020
DOI: 10.3390/genes11030237
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Sex Pheromone Discrimination by a UDP-Glycosyltransferase in Drosophila melanogaster

Abstract: The detection and processing of chemical stimuli involve coordinated neuronal networks that process sensory information. This allows animals, such as the model species Drosophila melanogaster, to detect food sources and to choose a potential mate. In peripheral olfactory tissues, several classes of proteins are acting to modulate the detection of chemosensory signals. This includes odorant-binding proteins together with odorant-degrading enzymes (ODEs). These enzymes, which primarily act to eliminate toxic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…For example, UGT201D3 was involved in the resistance of T. cinnabarinus to abamectin (M. Y. Wang et al, 2020) and UGT2B17 to chlorantraniliprole in P. xylostella (X. Li et al, 2017). And Fraichard et al (2020) found that DmelUGT36E1 was involved in sex pheromone discrimination. On this basis, we suggest that the analysis of D. melanogaster ODEs can start from GSTs and UGTs.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, UGT201D3 was involved in the resistance of T. cinnabarinus to abamectin (M. Y. Wang et al, 2020) and UGT2B17 to chlorantraniliprole in P. xylostella (X. Li et al, 2017). And Fraichard et al (2020) found that DmelUGT36E1 was involved in sex pheromone discrimination. On this basis, we suggest that the analysis of D. melanogaster ODEs can start from GSTs and UGTs.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Li et al, 2017). And Fraichard et al (2020) found that DmelUGT36E1 was involved in sex pheromone discrimination. On this basis, we suggest that the analysis of D. melanogaster ODEs can start from GSTs and UGTs.…”
Section: The Other 12 Sr-bs May Function In Transport and Degradationmentioning
confidence: 99%
“…In insects, their roles in detoxifying plant defenses [45] and in olfaction are especially well studied [46]. Multiple UGTs have sex-biased expression in Drosophila [47], including one that has to be downregulated in male antennae to play its role in sex pheromone sensing [48]. Future studies could use dual-luciferase reporter assays to test for binding between the api-mir-3023 miRNA and this gene.…”
Section: Discussionmentioning
confidence: 99%
“…Although the cellular mechanism related to this locus is unknown, drosophila homologs for UGT1A1 and UGT2A2 are known to play an important role in olfactory functions. Reduced detection of pheromone and other functional defects were observed with tissue-specific mutations and RNAi-mediated knockdown of UGT1A1 and UGT2A2 [59].…”
Section: Genetic Factors As a Determinant For Covid-19 Associated Odmentioning
confidence: 99%